Rhenium tetrazolato complexes coordinated to thioalkyl-functionalised phenanthroline ligands: Synthesis, photophysical characterisation, and incubation in live HeLa cells - Werrett, Melissa; Wright, Phillip; Simpson, Peter; Raiteri, Paolo; Skelton, B.; Stagni, S.; Buckley, A.; Rigby, P.; Massi, Massimiliano (2015)
© The Royal Society of Chemistry 2015. Three new complexes of formulation fac-[Re(CO)3(diim)L], where diim is either 1,10-phenanthroline or 1,10-phenanthroline functionalised at position 5 by a thioalkyl chain, and L is either a chloro or aryltetrazolato ancillary ligand, were synthesised and photophysically characterised. The complexes exhibit phosphorescent emission with maxima around 600 nm, originating from triplet metal-to-ligand charge transfer states with partially mixed ligand-to-ligand charge transfer character. The emission is relatively long-lived, within the 200-400 ns range, and with quantum yields of 2-4%. The complexes were trialed as cellular markers in live HeLa cells, along with two previously reported rhenium tetrazolato complexes bound to unsubstituted 1,10-phenanthroline. All five complexes exhibit good cellular uptake and non-specific perinuclear localisation. Upon excitation at 405 nm, the emission from the rhenium complexes could be clearly distinguished from autofluorescence, as demonstrated by spectral detection within the live cells. Four of the complexes did not appear to be toxic, however prolonged excitation could result in membrane blebbing. No major sign of photobleaching was detected upon multiple imaging on the same cell sample.